Financing for sustainable development in Latin America and the Caribbean (ECLAC [Santiago]CL, 2001)
Contains an analysis of the six trends that have marked financing for sustainable development since 1992, in Latin America and the Caribbean. Emphasizes the need to move the issues forward especially with regard to national policies on financing for sustainable development.
Bibliography: p. 73-76